The Influence of Work Engagement on Employee Performance at PT Java Connection Yogyakarta - Ilham, Muhammad (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research aims to analyze and test work engagement on the performance of PT Java Connection employees. This research method uses a quantitative method, with a sample size of 57 where sampling uses a saturated sampling technique, while the data analysis method uses descriptive methods and SEM-PLS. The results of this research show that there is a positive and significant influence between work engagement and employee performance at PT Java Connection. This can be seen from the comparison of t-statistic values ​​and t-table values ​​(3.652 > 1.96) as well as significant p values ​​smaller than 0.05 (0.000 < 0.05), the magnitude of the influence between work involvement and performance is 10.9%, where the remaining 89.1% is influenced by other factors outside this research.